Keberlanjutan Kelompok Tani dalam Pengembangan Agribisnis pada Usahatani Padi Sawah di Kecamatan Konda Kabupaten Konawe Selatan - Mastri Susilo; Dasmin Sidu; Anas Nikoyan (Jurnal Sosio Agribisnis, 2022)
The purpose of the study was to analyze the sustainability of farmer groups in agribusiness development in Paddies Farming (Research In Konda District, South Konawe Regency). The research was carried out in Konda Subdistrict, Konawe Selatan Regency, precisely in 3 villages namely Masagena Village, Cialam Jaya Village and Pombulaa Jaya Village in March - May 2021. Informants in this study were farmers, farmer group leaders, to villages and agricultural extension workers. Determination of informants using purposive sampling technique and Snowball Side. The focus in this study is institutional sustainability (input, process and output). The data analysis used is descriptive qualitative analysis. The results showed that the institutional sustainability of farmer groups in agribusiness development in lowland rice farming in Konda District, South Konawe Regency, was mostly included in the less sustainable category.Keywords: sustainability; farmer group; paddies farming.